2014
DOI: 10.1161/circinterventions.113.001197
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Reload Before Elective Percutaneous Coronary Intervention

Abstract: Background-Microvascular obstruction seems to predict poor outcome in patients undergoing elective percutaneous coronary intervention (PCI), but the underlying mechanism is still unclear. We analyzed whether serum thromboxane B 2 , a stable metabolite of thromboxane A 2 , may be implicated in post-PCI microvascular obstruction. Methods and Results-We enrolled 91 patients (74 males, 66±10 years) on chronic low-dose aspirin therapy (aspirin, 100 mg daily) scheduled for elective PCI and randomly assigned to recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 39 publications
0
6
0
4
Order By: Relevance
“…Sample Size Calculation Preliminary data reported a higher rate of pathologic post-procedural MBG in women (50%) compared to men (30%) despite a TIMI flow grade 3 after PCI [80].…”
Section: Statistical Analysis Planmentioning
confidence: 99%
“…Sample Size Calculation Preliminary data reported a higher rate of pathologic post-procedural MBG in women (50%) compared to men (30%) despite a TIMI flow grade 3 after PCI [80].…”
Section: Statistical Analysis Planmentioning
confidence: 99%
“…Many studies have shown that aspirin treatment caused a strong decrease in NF-κB activation, inhibitor of IκB-α phosphorylation together with translocation of NF-κB p65 to nucleus and IKK-β activation ( Shi et al, 2017 ). And many studies have shown that aspirin could improve I/R injury indexes as a positive and meaningful drug in the treatment of cardiovascular and cerebrovascular diseases ( Basili et al, 2014 ). So we chose aspirin as the positive control to compare with the effect of GC in order to elucidate the exact mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…12 Moreover, a 325-mg LD of aspirin in patients on chronic low dose of aspirin undergoing elective PCI, has been shown to improve the myocardial reperfusion and myocardial injury indexes. 13 Features of angiographic complexity and potential impact on outcome were not reported in these 2 studies. However, a pre-interventional LD of 150-300 mg aspirin orally-or 75-150 mg intravenously -is considered the standard of care as per guideline suggestions, regardless of PCI complexity.…”
Section: Preprocedural Treatmentmentioning
confidence: 98%